Social Movement in Framing Perspective: Omnibus Law Protest in Indonesia: Gerakan Sosial dalam Perspektif Framing: Protes Terhadap Omnibus Law di Indonesia - Jamil, Achmad; Briandana, Rizki; Marta, Rustono Farady (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
This study aims to provide a framing perspective on the study of development communication. This study explains the causes of the emergence of social movements in Indonesia in rejecting the Omnibus Law. The protests against the Omnibus Law that occurred in various cities in Indonesia as a form of resistance to government policies were examined from the perspective of framing theory. The method used is text analysis with Robert N Entman’s framing framework. The unit of analysis is the Omnibus Law protest news published in Tempo Magazine in October 2020. The results of this study indicate that social movements to reject the Omnibus Law were carried out by various elements of society, ranging from workers, students, and other elements of society. Even though the Omnibus Law was finally signed by President Joko Widodo on October 5, 2020, the protest effort remained an important note that this law has many loopholes that are considered to be detrimental to elements of society, potentially damaging the environment, and weakening government authority area.